Imaging in gynecological disease (19): clinical and ultrasound features of extragastrointestinal stromal tumors (eGIST). (11th October 2020) - Ambrosio, M.; Testa, A. C.; Moro, F.; Franchi, D.; Scifo, M. C.; Rams, N.; Epstein, E.; Alcazar, J. L.; Hidalgo, J. J.; Van Holsbeke, C.; Burgetova, A.; Dundr, P.; et al.
ABSTRACT: Objective: To describe the clinical and sonographic characteristics of extragastrointestinal stromal tumors (eGISTs). Methods: This was a retrospective multicenter study. The data of patients with a histological diagnosis of eGIST who had undergone preoperative ultrasound examination were retrieved from the databases of nine large European gynecologic oncology centers. One investigator from each center reviewed stored images and ultrasound reports, and described the lesions using the terminology of the International Ovarian Tumor Analysis and Morphological Uterus Sonographic Assessment groups, following a predefined ultrasound evaluation form. Clinical, surgical and pathological information was also recorded. Results: Thirty‐five women with an eGIST were identified; in 17 cases, the findings were incidental, and 18 cases were symptomatic. Median age was 57 years (range, 21–85 years). Tumor marker CA 125 was available in 23 (65.7%) patients, with a median level of 23 U/mL (range, 7–403 U/mL). The vast majority of eGISTs were intraperitoneal lesions ( n  = 32 (91.4%)); the remaining lesions were retroperitoneal ( n  = 2 (5.7%)) or preperitoneal ( n  = 1 (2.9%)). The most common site of the tumor was the abdomen ( n  = 23 (65.7%)), and less frequently the pelvis ( n  = 12 (34.3%)). eGISTs were typically large (median largest diameter, 79 mm) solid ( n  = 31 (88.6%)) tumors, and were less frequently multilocular‐solid tumors ( n  = 4 (11.4%)). The echogenicity of solid tumors was uniform in 8/31 (25.8%) cases, which were all hypoechogenic. Twenty‐three solid eGISTs were non‐uniform, either with mixed echogenicity (9/23 (39.1%)) or with cystic areas (14/23 (60.9%)). The tumor shape was mainly lobular ( n  = 19 (54.3%)) or irregular ( n  = 10 (28.6%)). Tumors were typically richly vascularized (color score of 3 or 4, n  = 31 (88.6%)) with no shadowing ( n  = 31 (88.6%)). Based on pattern recognition, eGISTs were usually correctly classified as a malignant lesion in the ultrasound reports ( n  = 32 (91.4%)), and the specific diagnosis of eGIST was the most frequent differential diagnosis ( n  = 16 (45.7%)), followed by primary ovarian cancer ( n  = 5 (14.3%)), lymphoma ( n  = 2 (5.7%)) and pedunculated uterine fibroid ( n  = 2 (5.7%)). Conclusions: On ultrasound, eGISTs were usually solid, non‐uniform pelvic or abdominal lobular tumors of mixed echogenicity, with or without cystic areas, with rich vascularization and no shadowing. The presence of a tumor with these features, without connection to the bowel wall, and not originating from the uterus or adnexa, is highly suspicious for eGIST. Copyright © 2020 ISUOG. Published by John Wiley & Sons Ltd.